Early Detection of Javanese Phonological Awareness of Grade 4 Elementary School Students - Endang Sri Maruti (Procedia of Social Sciences and Humanities, 2021)
This study aim to detect the phonological awareness of Javanese in elementary school grade 4 students early through the distance learning process. To be able to determine the level of awareness of children's phonology, one indicator is to look at the child's ability to write and read Javanese text. This research is a descriptive qualitative type. Data was collected by archiving all assignments related to writing and reading Javanese text sent by students through the WhatsApp application. The collected data were then analyzed descriptively. The results showed that grade 4 elementary school students made many phonological errors when writing and reading Javanese text. The most common mistakes are when writing vowels /a/ and reading consonants /dh/ and /th/. Based on the many errors, it can be concluded that the phonological awareness of Javanese elementary school students is still low, or it can be said to be less aware.